Nutritional status and oral health: an interdisciplinary challenge of health education in students of an educational institution from Medellin - Colombia (2020)
ABSTRACT: Introduction: “There is a two-way relationship between health, diet and nutrition” J AcadNutrDiet. 2013 May; 113 (5): 693-701. doi: 10.1016 / j.jand. 2013.03.001.). The oral health situation compromises an individual’s ability to consume food, consequently, the nutritional status; likewise, diet and nutrition affect the development and integrity of oral structures and their functioning. Some studies have shown that in populations with low sugar consumption, tooth-decay levels are also lower. As a result, a multidisciplinary articulation between nutrition and oral health to develop comprehensive research and education actions in health is necessary. Objective: To identify the relation between nutritional state and oral hygiene in schoolchildren of a public institution in Medellin-Colombia. Methodology: Dental and nutritional assessments were done on 372 schoolchildren between 8 and 12 years of age, as well as the Simplified Oral Hygiene Index (SOHI), obtaining good, fair, and bad hygiene. For the Nutritional Status, an anthropometric evaluation (weight, height, age, and gender) was performed based on the BMI / E, using the WHO's AnthroPlus, obtaining the classification of: Thinness, Risk of thinness, Adequate weight, Overweight and Obesity. The “SOHI” variables were matched against the “Nutritional Status” numbers. Results: The overweight index was 26.07%, the obesity index was 10.75%, the proper weight was found in 53.22% of the children, 8.60% were at risk of thinness, and 1.34% were thin. Of the 62.4% that showed good oral-hygiene, 53.4% had adequate weight, 27.6% were overweight and 11.2% were obese. Similarly, of the 37.4% that indicated fair oral-hygiene, 53.2% had adequate weight, 23% were overweight and 10.1% were obese. Finally, 0.3% showed poor oral hygiene, of which 100% were overweight. According to ENSAB IV, 92.06% of Colombian school children show signs of tooth-decay; in our case, the overweight problem deserves special attention when compared to the oral-hygiene issue. Conclusions: Among the factors that lead to the development of dental decay, is the consumption of a cariogenic diet coupled with unhealthy habits such as poor oral hygiene. This calls for a joined effort between nutrition and dentistry professionals in the planning and execution of educational activities for health.